Christianity in India : sociological investigations - Parathazham, Paul (Bangalore Dharmaram Publications, 2013)
Lectures delivered at Dharmaram Vidya Kshetram, Bangalore during 23-24 August 2012.
Includes bibliographical references.
Keywords: Christianity -- Social aspects -- India; Religion and sociology -- India